ANALISIS PENERAPAN BACAAN TILAWATI TERHADAP KUALITAS TAHFIDZ SANTRI PONDOK PESANTREN TAHFIDZ MUHAMMADIYAH AL FATTAH NGANTANG - Ubaidillah Al Affan; Eni Fariyatul Fahyuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe and analyze the implementation of the Tilawati methodusing the Rost melody to improve the quality of Qur’anic recitation and memorizationamong students at Pondok Pesantren Tahfidz Muhammadiyah Al-Fattah Ngantang,Malang. The background of this research is based on the need for a method that isnot only technically effective but also capable of creating a pleasant and motivatinglearning environment. The Tilawati method was chosen because it integrates theelements of tajweed, articulation (makharijul huruf), and tartil training with a musicalapproach, one of which includes the use of the Rost melody. This research uses adescriptive qualitative approach, with data collected through observation,interviews, and documentation. The findings show that the use of the Rost melodyin the Tilawati method significantly enhances students' ability to recite the Qur’ancorrectly, according to tajweed and articulation rules. Moreover, the melodicapproach proves effective in accelerating the memorization process andstrengthening the students’ memory of Qur’anic verses. A well-structured dailylearning schedule, from dawn to night, combined with an objective evaluationsystem, also contributes to the success of the tahfidz program at the pesantren. Inconclusion, the Tilawati method accompanied by the Rost melody is proven to beeffective in improving the quality of Qur’anic recitation and memorization, while alsomaking a significant contribution to the achievement of memorization targets andthe development of Qur’anic character among students. This method is worth furtherdevelopment as an inspiring model in broader tahfidz education contexts.